827. SORBUS HENRYI: Rosaceae. (22nd April 2016) - Rushforth, Keith
Summary: Sorbus henryi Rehder from the Mount Omei region in Sichuan, remains a rarity in cultivation. Its nomenclature and taxonomy are discussed. A fruiting specimen and flowers are illustrated.